National Award to KVK, Venkataramannagudem, Andhra Pradesh - Janakiram, T (Indian Horticulture, 2020)
Dr. YSR Horticultural University, is second of its kind in the country, functioning with four Horticultural colleges, four Horticulture Polytechnics, twenty Research Stations, four affiliated private Horticultural Colleges, seven private Horticultural Polytechnics and four Krishi Vigyan Kendras in Andhra Pradesh with its headquarters at Venkataramannagudem, West Godavari district, Andhra Pradesh.